The Interrelation of Language and Thought in the Text - TONOYAN, TADEVOS (Bulletin of Yerevan University B: Philology, 2021)
The tendency of comparing linguistics with literary criticism noticed especially in the XX century is gradually deepening due to the fact that, as linguistic reality, especially the form and content of the text in their various aspects, i.e. structural, cultural,linguistic, philosophical, etc. are studied.From the linguistic study of the literary text literary-cultural problems can logicallybe deduced and solved, as the ideas raised in a literary work (content plane) are always in search of suitable language basis (form). Literary criticism puts the text in the horizontal plane alongside other texts: the comparison is made in the parallels of two identical internal texts at a specific time. The text, first of all, anchored in the panorama of various phenomena (literature, history, beliefs, tips on the being of people, religion, customs, lifestyle, etc.) and also being analyzed out of specific time enables to find out what structure-phenomenon of language awareness the given text represents. The study of the structure and content of the text could enable to reveal the peculiarities of thinking of the people speaking that language and the system of cultural values.
Keywords: language awareness, system of values, text, talk, think